Club-based vs. hospital-guided rehabilitation after ACL reconstruction in football participants: a two-year prospective cohort study - Han, Zhe; Sun, Peng; Chen, Tianwu; Dong, Yu (Frontiers in Sports and Active Living, 2025)
BackgroundAnterior cruciate ligament (ACL) injury is a common and serious sports injury in football. Although reconstruction surgery can restore joint stability, postoperative rehabilitation strategies play a critical role in long-term outcomes, particularly return to sport (RTS). However, comparative studies on the long-term efficacy of hospital-guided vs. club-based rehabilitation programs remain limited.PurposeTo compare the two-year clinical outcomes and RTS of hospital-guided and club-based rehabilitation programs following ACL reconstruction in football participants.MethodsThis prospective cohort study enrolled 40 football participants who underwent primary ACL reconstruction. Participants were assigned to two groups based on rehabilitation modality: hospital-guided rehabilitation (n = 20), which emphasized basic joint function recovery, and club-based rehabilitation (n = 20), which focused on sport-specific physical conditioning and performance enhancement. Outcome measures included subjective functional scores: Tegner Activity Score (TAS), Marx Activity Rating Scale (MARS), International Knee Documentation Committee (IKDC) subjective score, Lysholm Knee Rating Scale (LKSS), and Anterior Cruciate Ligament-Return to Sport after Injury (ACL-RSI), as well as objective knee function [effusion, range of motion (ROM), and joint stability], time to return to training and competition, and re-injury rate.ResultsThe two groups were comparable at baseline. The club-based group demonstrated significantly better outcomes in TAS (8.5 ± 1.4 vs. 7.2 ± 1.0, p = 0.006), MARS (12.7 ± 2.8 vs. 10.6 ± 2.7, p = 0.019), and ACL-RSI (73.3 ± 21.4 vs. 54.3 ± 18.7, p = 0.003). Time to return to training and competitive play was significantly shorter in the club-based group. No significant differences were observed in ROM, joint stability, or re-injury rate between groups.ConclusionClub-based rehabilitation led to superior subjective function, greater psychological readiness, and earlier return to sport compared to hospital-guided programs, without increasing re-injury risk. These findings support the effectiveness of sport-specific rehabilitation in football players after ACL reconstruction, though further studies are needed to evaluate long-term safety and cost-effectiveness.